Effect of water to binder ratio, polycarboxylate superplasticizer and metakaolin dosages on rheological and viscoelastic properties of fresh metakaolin-air lime pastes. (15th December 2022) - Zhang, Dajiang; Xu, Dong; Liu, Hui; Wang, Yali; Wang, Hui; Wang, Jianfeng; Cui, Suping; Wang, Dongmin
Abstract: As an ancient architectural restoration material, hydraulic lime has good early properties, which is necessary to ensure its successful application. Metakaolin-air lime (MK-AL) composite material as a kind of hydraulic lime, the initial fluidity, macroscopic rheological properties, viscoelasticity and dissolution-early hydration are systematically investigated by setting different water to binder (w/b) ratios, polycarboxylate superplasticizer (SP) and metakaolin dosages. The results showed that the initial fluidity of MK-AL pastes has a more obvious improvement by adding SP. The rheological behavior of MK-AL paste was well characterized by both the Bingham model and H–B model. The reduction of yield stress and plastic viscosity on account of the better dispersion of particles in MK-AL paste. The rheological behavior expresses shear thickening without SP and shear thinning with SP in MK-AL paste are revealed. The viscoelastic transformation is illustrated by the macroscopic viscosity index, elastic index, storage modulus, loss modulus, solid-liquid balance and fluidity index parameters, these parameters have a reduction to a large degree with increasing w/b ratios and SP dosage, while the variation of metakaolin dosage has relatively little impact. The increase in w/b ratio and SP dosage promote the dispersion and dissolution of the particles in the aqueous solution, and the strong dispersive capacity delays the process that particles heap up rapidly and network structure formation in MK-AL pastes. Furthermore, the exothermic rate of the two hydration stages is reduced significantly, as well as the appearance of the exothermic peak of hydration is delayed. Highlights: Initial fluidity of MK-AL paste is improved significantly by adding SP. Rheological behavior of MK-AL paste is characterized by Bingham and H–B models. Viscoelastic transformation of MK-AL paste is non-contact and in-situ tested. Strong dispersive capacity delay particles heap up and network structure formation. Heat release rate of hydration stage is reduced with enlarging w/b ratio or SP dosage.